Nabavna politika šolske knjižnice med pritiskom finančne luknje in potrebami (željami) uporabnikov - Napast, Klara (Šolska knjižnica, 2016)
An important segment of the work of school librarians is the acquisitions policy. This has been especially evident in recent years, as the funds for new acquisitions are being reduced. The school allocates a portion of the appropriations for material resources to the acquisition of library materials. The school's head teacher specifies the sum to be allocated to the annual updating of the library collection. The current situation only allows for necessary purchases or the minimum updating of the collection. The financial situation is therefore hindering us from complying with the Rules on Conditions for Providing Library Services as a Public Service (2003), which expressly order the supplementing of library collections. Nevertheless, we are doing our best at the library to provide a diverse and up-to-date library collection. Regardless of the financial situation (or even more so because of it), the criteria that are most important for the acquisition of new materials are: updates in accordance with the curricula (the materials needed by teachers to plan and carry out lessons, and by students to follow lessons; required reading; preparing for competitions, etc.); professional innovations; new editions by individual collections; and users' needs. Acquisition is based on professional deliberation, taking into account financial abilities and the needs of users. It is therefore very important that the updating of material is structured by priority. In recent years, the acquisitions policy has been becoming a real challenge. We, the librarians, have to promote the library, the books and the library activity by ourselves in contribution to educational work, focusing above all on its positive effects, and thus obtain the funds needed to purchase new, much-needed material.
Keywords: nabava; nabavna politika; osnovne šole; šolske knjižnice; zakonodaja